AKTYWNOŚCI STYMULUJĄCE REFLEKSJĘ W NAUCZANIU JĘZYKA PISANEGO W WIRTUALNEJ KLASIE - Mokwa-Tarnowska, Iwona (Neofilolog, 2019)
The paper aims to show how to engage students attending an online language course in various activities which by stimulating reflection enhance the learning process and result in better learning outcomes. By blending cognitivist, constructivist, constructionist and behavioural ideas, course developers and tutors can produce materials and use methods which satisfy the varied needs of adults who want to improve their writing skills. Such a blend leads to a unique design, which can be achieved by tools available in a virtual learning environment. Course participants will be more adequately prepared for writing genuine texts in the future through use of such activities as working with authentic resources integrated with different tasks and assignments to stimulate reflection; studying under the supervision and guidance of the tutor; participating in collaborative projects to promote learner autonomy; developing new knowledge through meaning-making discussions; doing peer review as well as summative, formative assessment, and self-assessment. Experience of these ways of working will help the participants to eventually become self-regulated, lifelong learners.